Fibre reinforced polymer concrete structures – opportunities and concerns - Mat Noor, N.A.; Mohamed, H. (2009)
In the civil engineering industry, deterioration of concrete structures is one of the major concerns in the construction field nowadays. Some of the earlier degradation of structures may caused by design or construction defects where in some cases a lower grade concrete has been supplied during constructions. Therefore, retrofitting of those defect reinforced concrete structures and also strengthening of insufficient capacity concrete structural elements has inevitably become an important activities in civil engineering. Instead of the old approach to demolish and reconstruct the buildings, structural repair and rehabilitation of reinforced concrete structures is becoming an ideal option for all deteriorated and damaged structures to restore, enhance the load bearing capacity and increase the life span of the structure. The strengthening of concrete structures with externally bonded reinforcement is generally done using either steel plates or Fibre reinforced polymer (FRP)composites system. However, the use of FRP composite materials for both new construction and strengthening of reinforced concrete structures has increased rapidly and gradually replace the steel plate method due to great advantages of FRP. The main objective of this research work is to evaluate and investigate the effectiveness of using Glass Fibre Reinforced Polymers (GFRP) to strengthen early age (green) concrete which is a very poor concrete grade. From the studies and analysis, high fatigue strength and high stiffness properties of the GFRP composites strengthening system give a high satisfaction results in improving the strength of all the concrete specimens tested.